ANALISIS PENGARUH GAYA HIDUP WANITA MODERN TERHADAP PERMINTAAN KONSUMSI KOSMETIK DI KOTA SURAKARTA - Kusdiyanto, Kusdiyanto (Universitas Muhammadiyah Surakarta, 2005)
This study aims to examine the significant influence of womenâs style on the demand ofcosmetic consumption in Surakarta. The frequency of cosmetic consumption in terms of its kindsand price significantly influences the demand of cosmetic consumption, Thus, it was confirmed. Inpartial (r), the price of cosmetics is the most dominant variable in determining the demand ofcosmetics. Every a 1 % price increase could raise the cosmetic consumption of 0.891 (inferiorgoods), but itâs kind could raise the cosmetic consumption of 0.753, and its frequency could raisethe cosmetic consumption of 0.188. Through autocorrelation, multicollinearity, andheteroscedasticity test, the result of this study showed that there was no real difference. Theinfluencing model of frequency of cosmetic consumption in terms of its kind and price on thedemand of cosmetic in double regression equation could be used the significant influence ifindependent variables on its dependent.